(3-√2)*(5+√8)= (2+√15)*(√5-√3) (4√t-5√s)^2 (x+√y)*(3x-4√y) (2√a+√b)*(√a-5√b)

(3-√2)*(5+√8)= (2+√15)*(√5-√3) (4√t-5√s)^2 (x+√y)*(3x-4√y) (2√a+√b)*(√a-5√b)
Гость
Ответ(ы) на вопрос:
Гость
1) (3-√2)(5+√8)=15-5√2+3√8-√16 =15 -5√2+6√2-4=11+√2 2) (2+√15)(√5-√3)=2√5+√75-2√3-√45=2√5+5√3-2√3-3√5=3√3 -√5 3) (4√t -5√s)² =(4√t)² - 2*4√t*5√s+(5√s)² = 16t-40√(ts)+25s 4) (x+√y)(3x-4√y)=3x²+3x√y-4x√y-4y=3x²-x√y-4y 5) (2√a+√b)(√a-5√b)=2a+√(ab)-10√(ab)-5b=2a-9√(ab)-5b
Не нашли ответ?
Ответить на вопрос
Похожие вопросы